The University – a Space for Building Community and Trust - Chrobak, Stanisław (Forum Pedagogiczne, 2019)
The University is constantly subject to a process of intense transformations. The diversity of social needs and expectations towards university education requires that the academic community analyze its current status, future challenges and consider initiatives that address these challenges. Thus, emphasizing the significance of universitas, as a community of teaching and learning (universitas studiorum et studentium), it is worth investigating how to build this community without losing fundamental values in massive studies. The university fulfills its own purpose when in a specific community that employs scientific creativity and research, it leads a person to development of their versatile spiritual potential of mind, will, heart, and a formation of the whole person.